2019
DOI: 10.3892/or.2019.7338
|View full text |Cite
|
Sign up to set email alerts
|

DDR1 promotes breast tumor growth by suppressing antitumor immunity

Abstract: Breast cancer is the second leading cause of cancer-associated mortality among women worldwide. Triple-negative breast cancer (TNBC) accounts for 15-20% of all breast cancers and is defined by its aggressive nature and limited treatment options. Therefore, there is an urgent need to develop effective therapies for TNBC in order to improve breast cancer outcomes, as targeted therapies have done in other subtypes of breast cancer. Discoidin domain receptor tyrosine kinase 1 (DDR1) is activated by collagens, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…How DDRs induce cancer signaling is another critical question, although we established an important connection between DDR1 signaling and the β-catenin pathway (42). Last, but not least, recent reports uncovered unsuspected DDR roles in CRC immune evasion (61,62). How these receptors contribute to this cancer hallmark is a basic and clinical question because DDR signaling inhibition could define a therapeutic strategy to reduce metastatic development and sensitize CRC to immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…How DDRs induce cancer signaling is another critical question, although we established an important connection between DDR1 signaling and the β-catenin pathway (42). Last, but not least, recent reports uncovered unsuspected DDR roles in CRC immune evasion (61,62). How these receptors contribute to this cancer hallmark is a basic and clinical question because DDR signaling inhibition could define a therapeutic strategy to reduce metastatic development and sensitize CRC to immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Whether DDR2 has a similar role in microsatellite-stable CRC cells remains to be tested. Similarly, it was suggested that DDR1 promotes breast tumor growth by suppressing the anti-tumor immunity (62). How exactly and in which circumstances DDR1 and DDR2 may regulate human tumor evasion, particularly in CRC, deserve further investigation.…”
Section: Ddr2 In Crc Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, COL8A1 products belong to extracellular matrix protein and serve as one of the nineteen human collagens, which are important components of the breast cancer stroma. It is possible that COL8A1 participates in the communication of breast cancer cells and microenvironments [61]. Second, COL8A1 plays important role in modulating migration, proliferation, and adhesion of tumor cells [62].…”
Section: Discussionmentioning
confidence: 99%
“…36 For example, Zhong et al disclosed that DDR1 augmentation induced tumorigenesis via hindering antitumor immunity in breast cancer. 37 Chou et al found that suppression of DDR1 restrained cell growth and accelerated apoptosis in oral cancer. 38 Moreover, the previous study indicated that DDR1 silencing impeded tumor progression in CRC by interacting with miR-199a-5p.…”
Section: Discussionmentioning
confidence: 99%